A New Type of Scaling Relations to Assess the Accuracy of Computational Predictions of Catalytic Activities Applied to the Oxygen Evolution Reaction. Issue 7 (14th March 2017) - Briquet, Ludovic G. V.; Sarwar, Misbah; Mugo, Jane; Jones, Glenn; Calle‐Vallejo, Federico
Abstract: Experimentally, it is well known that the overpotentials for the oxygen evolution reaction (OER) on RuO2 and IrO2 are similar and rather low. The question is whether widespread computational electrochemistry models based on adsorption thermodynamics are capable of reproducing such observations. Making use of DFT results of revised Perdew–Burke–Ernzerhof (RPBE) and Perdew–Burke–Ernzerhof (PBE) functionals from six different codes and various types of pseudopotentials, we show that whereas IrO2 is consistently predicted to have low overpotentials, RuO2 is predicted to have large overpotentials. A new methodology based on adsorption‐energy scaling relations shows that the inaccurate prediction for RuO2 stems from its anomalous adsorption energies of oxygen/oxygenates. Including explicit water solvation and using functionals that account for van der Waals interactions such as vdW‐DF, vdW‐DF2 and optPBE‐vdW modifies appropriately the adsorption energies so that both oxides are predicted to be highly active. Abstract : Finding good catalysis gOERs The most widespread computational method used to predict oxygen evolution activities of oxide catalysts does not predict RuO2 to be active at the GGA level. The origin of this anomaly is detected using a new type of scaling relations. Besides, the problem is mitigated using explicit solvation and functionals that account for van der Waals interactions.